COMPLICATIONS OF THE COMPUTED TOMOGRAPHY GUIDED TRANSTHORACIC BIOPSY OF THE LUNG - Khan, Abdur Rehman; Yousaf, Muhammad; Javaid, Arshad; Khan, Ijaz (Journal of Postgraduate Medical Institute, 2011)
Objective: To evaluate the frequency of pneumothorax and hemoptysis after computed tomography (CT)- guided percutaneous co-axial cutting needle biopsy of lung lesions. Material and Methods: This was a descriptive study of patients who underwent CT guided percutaneous coaxial cutting needle biopsy of lung lesions at department of Radiology, Postgraduate Medical Institute, Lady Reading Hospital, Peshawar from August 2004 to June 2005. CT scan of the lung at the level of pleural puncture was taken immediately after biopsy and an X-ray chest in upright position was taken after 04 hours for evidence of pneumothorax. Pneumothorax and hemoptysis were recorded. Results: Out of 53 patients, 26 (49%) were male and 27 (51%) were female with age ranging from 06-80 years. Of 53 biopsies, in 49 cases tissue sample was sufficient for histological diagnosis (Diagnostic yield 92.45%). Out of 53 biopsies, 32 (60.4%) were histologically malignant, 17 (32.1%) were benign and 4 (7.5%) were non-representative, normal lung tissue or inadequate tissues. Overall complication rate was 9.43% (n=5/53). Hemoptysis occurred in 4/53 (7.45%). Pneumothorax occurred in 1.9% (n=1/53) patients. No patient required chest tube insertion. There was no major complication or death. Conclusion: CT guided percutaneous coaxial cutting needle biopsy of the lung lesions is a safe and effective procedure.